Contrast arthrography of the equine temporomandibular joint - Kim, Clara S.; Reisbig, Nathalie A.; Carmalt, James L. (Frontiers in Veterinary Science, 2024)
Background: Disorders of the equine temporomandibular joint (TMJ) cause clinical problems and detailed investigations of this joint are becoming more common. Specialist radiographic projections have the potential to highlight osseous abnormalities; however, the ability to assess the intra-articular soft tissue structures is currently limited to computed tomography (with, or without contrast enhancement) or magnetic resonance imaging. Both modalities are expensive and not readily accessible.Objective: To develop a technique of contrast arthrography of both compartments of the equine TMJ in cadavers and then perform the refined technique in three living horses as a proof-of-principle.A descriptive, experimental, study.Methods: Contrast arthrography of the discomandibular and discotemporal joint compartments of both TMJs was performed in 12 cadaveric equine heads using needles placed in the caudal pouches of the respective joint compartments. Radiographs were taken using previously published techniques, repeated with the mouth open and after air had been injected into the joints, to perform a doublecontrast study. The TMJs of three healthy horses were subsequently examined to determine the validity of the procedure in live animals.Results: Single and double-contrast arthrography allowed delineation of the dorsal and ventral surfaces of the intra-articular disc in addition to filling the rostral and caudal joint pouches of the independent joint compartments. Contrast extravasation was common, and in two instances iatrogenic disc penetration resulted in the false diagnosis of pathologic disc perforation. The techniques were well tolerated in all three live horses.Conclusions: Contrast arthrography allows interpretation of intra-articular soft tissue structures, but caution is advised in diagnosing intra-articular disc perforation. Even with experience, accessing the discomandibular joint can be challenging.